High frequency surface wave radar demonstrator - Burger, Johann (Department of Electrical Engineering, 2019)
High Frequency Surface Wave Radar (HFSWR) is used around the globe for the mapping of sea currents and coastal monitoring of the Exclusive Economic Zone. Decision to build an HF radar at the University of Cape Town (UCT) was made by Daniel O’Hagan and Andrew Wilkinson in February 2015 immediately after seeing a demonstration of the CODAR system at IMT. Their intention was subsequently discussed at several meetings, including a South African Radar Interest Group (SARIG) meeting and one at IMT in order to gauge interest and raise funding. There was both interest (mainly for ocean current monitoring) and scepticism (expressed by CSIR and SARIG members) of the value of HF radar for ship monitoring. This reports the design, construction, test, and evaluation of the UCT HFSWR demonstrator. A modular approach was taken in its design and construction making it easy to replicate and upscale. A pillar of this work is to prove the feasibility of a software defined radar (SDR) based HF radar demonstrator. Every part of the demonstrator was designed and constructed from scratch as UCT had no prior HF activities, and therefore no legacy antennas or components to utilise. A low-cost RF frontend follows the HF antennas, which were also designed for this project. Combined with an SDR platforn known as the Red Pitaya (RP), a complete HF radar demonstrator was assembled and trials were conducted at the UCT rugby field and at the IMT facilities in Simon’s Town. A preliminary assessment of the results reveal the effects of Bragg resonance scatter and detection of two stationary targets (mountains) distinguishable by both range and azimuth. This assessment of the results indicates that the demonstrator is operational.